Kajian Psychological Carrying Capacity Pantai Kuta Bali Berdasarkan Beach Evaluation Structure dan Perceived Crowding - Ni Luh Putu Budastri; Ni Made Tirtawati; Anom Hery Suasapha (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2026)
This study aims to analyze the psychological carrying capacity of Kuta Beach based on tourists' evaluations of beach quality attributes (Beach Evaluation Structure) and perceived crowding. The study was motivated by the high intensity of tourist visitation, which has the potential to affect the quality of tourists' experiences and destination sustainability. A quantitative approach was employed involving 200 tourists who had visited Kuta Beach more than once. Data were collected through questionnaire surveys and analyzed using descriptive statistics. The results indicate that most Beach Evaluation Structure attributes, including cleanliness of beach environment, safety, and facilities and services, received positive evaluations from tourists. In contrast, the beach protection and management dimension received relatively lower evaluations, particularly regarding coastal erosion protection and the provision of environmental information. Furthermore, tourists acknowledged that Kuta Beach becomes crowded during certain periods; however, the level of crowding remained within an acceptable range and did not significantly diminish the quality of their tourism experience. Overall, the findings suggest that the psychological carrying capacity of Kuta Beach remains within an acceptable threshold, although early signs of pressure indicate the need for sustainable destination management. Keywords: psychological carrying capacity, beach evaluation structure, perceived crowding, Kuta Beach Bali